Development of Enterprise Competencies at Lithuanian Academy of Physical Education (Baltic Journal of Sport and Health Sciences, 2018)
The article deals with the problems of university teaching. It analyses the possibility to improve the quality oftraditional university teaching by introducing enterprise competencies and making them one of the outcomes oflearning.The authors present the results of the research that has been carried out using a method of a questionnaire at theLithuanian Academy of Physical Education. The aim of the study was to investigate the development of enterprisecompetencies in undergraduate population. The research was conducted in the Faculty of Sports Technologies andTourism at the Lithuanian Academy of Physical Education. The randomly selected sample consisted of 131 secondand fourth year students of sports and tourism management. The data obtained helped to draw the followingconclusions: traditional teaching methods prevail at the Lithuanian Academy of Physical Education; in the processof university studies students pay greater attention to theoretical knowledge than to the acquisition of practical skills;the second and the fourth year students of sports and tourism management lack systematic development of enterprisecompetencies in the process of teaching. In the scale of importance, the most appreciated enterprise competenciesare as follows: ability to communicate, computer literacy, knowledge of one’s capabilities, ability to work in a team;accordingly, the least appreciated enterprise competencies are as follows: ability to seek and to act on newopportunities, ability to analyse statistical data, ability to eliminate stressors, managing personal stress and stressfulsituations.Keywords: quality, university teaching, enterprise competencies.